The organic geochemical characterization: An indication of type of kerogen and maturity of early - Mid Jurassic shale in the Blue Nile formation - Shoieba, M.A. (American Institute of Physics Inc., 2018)
The heterogeneity and complexity of shale gas has become clear as the development of unconventional resources have improved. The Blue Nile Basin, is one of the many Mesozoic rift basins in Sudan associated with the Central African Rift System (CARS). It is located in the eastern part of the Republic of Sudan and has been the major focus for shale gas exploration due to the hydrocarbon found in the basin. But so far no success of discovery has been achieved because the shale gas potentiality of the study area is still unknown. The objective of this study is to assess the type of kerogen and maturity of the shale samples from the Blue Nile Formation within the Blue Nile Basin. This was done by employing organic geochemical methods such as pyrolysis gas chromatography (Py-GC) and petrographic analysis such as vitrinite reflectance (Ro). Ten representative shale samples from TW-1 well in the Blue Nile Formation have been used to assess the quality of the source rock. Pyrolysis GC analysis indicate that all the selected shale samples contain Type II kerogen that produces oil and gas. The Blue Nile Formation possesses vitrinite reflectance (Ro) of 0.60-0.65, indicating that the shale samples are mature in the oil window. Â© 2018 Author(s).